FEATURES OF THE NATIONAL POLICY OF MODERN CHINA AND NATIONAL MINORITIES - Н.Ә, Алдaбек; А.М., Нұржaевa (Journal of Oriental Studies, 2019)
This article examines the national policy of the PRC in relation to national minorities and its role in strengthening the unity of the state and interethnic relations. The results of the research can be used in political science related to the analysis of the state’s national policy in modern China, and can also be used in further theoretical development within the framework of political knowledge about “national politics”; to improve the effectiveness of national policy for the small peoples of the PRC and other mod- ern multinational countries. The methodology of the study is based on an interdisciplinary approach that encompasses social and political science. In the course of the research, scientific principles and methods of analysis, synthesis, comparison, as well as a comparative-historical method were used, which as a result helped to reveal the general and specific features of the research subject, prospects and qualitative characteristics of its development. Key words: national policy, PRC, national minorities.